Carotenogenesis diversification in phylogenetic lineages of Rhodophyta. Issue 3 (26th April 2016) - Takaichi, Shinichi; Yokoyama, Akiko; Mochimaru, Mari; Uchida, Hiroko; Murakami, Akio
Abstract : Carotenoid composition is very diverse in Rhodophyta. In this study, we investigated whether this variation is related to the phylogeny of this group. Rhodophyta consists of seven classes, and they can be divided into two groups on the basis of their morphology. The unicellular group (Cyanidiophyceae, Porphyridiophyceae, Rhodellophyceae, and Stylonematophyceae) contained only β‐carotene and zeaxanthin, "ZEA‐type carotenoids." In contrast, within the macrophytic group (Bangiophyceae, Compsopogonophyceae, and Florideophyceae), Compsopogonophyceae contained antheraxanthin in addition to ZEA‐type carotenoids, "ANT‐type carotenoids, " whereas Bangiophyceae contained α‐carotene and lutein along with ZEA‐type carotenoids, "LUT‐type carotenoids." Florideophyceae is divided into five subclasses. Ahnfeltiophycidae, Hildenbrandiophycidae, and Nemaliophycidae contained LUT‐type carotenoids. In Corallinophycidae, Hapalidiales and Lithophylloideae in Corallinales contained LUT‐type carotenoids, whereas Corallinoideae in Corallinales contained ANT‐type carotenoids. In Rhodymeniophycidae, most orders contained LUT‐type carotenoids; however, only Gracilariales contained ANT‐type carotenoids. There is a clear relationship between carotenoid composition and phylogenetics in Rhodophyta. Furthermore, we searched open genome databases of several red algae for references to the synthetic enzymes of the carotenoid types detected in this study. β‐Carotene and zeaxanthin might be synthesized from lycopene, as in land plants. Antheraxanthin might require zeaxanthin epoxydase, whereas α‐carotene and lutein might require two additional enzymes, as in land plants. Furthermore, Glaucophyta contained ZEA‐type carotenoids, and Cryptophyta contained β‐carotene, α‐carotene, and alloxanthin, whose acetylenic group might be synthesized from zeaxanthin by an unknown enzyme. Therefore, we conclude that the presence or absence of the four enzymes is related to diversification of carotenoid composition in these three phyla.